THE STUDY OF OCEAN CURRENT ENERGY POTENTIAL IN LEMBEH STRAIT USING 3-D HYDRODYNAMIC MODEL - Naufal - NIM 12913033 , Altof
In this final project, has been studied hydrodynamic process and current energy potential in Lembeh Strait, North Sulawesi. The study of the potential energy of ocean currents is divided into two main phase. The first phase is simulating the ocean current hydrodynamics in Lembeh Strait using 3-dimension barothropic hydrodynamic model using the ocean current in each open boundary based on the result obtained from the previous 2 dimension large model including the Moluka Sea and Celebes Sea using a barotropic model with tidal generating force on every open boundary. The next step is to map out and analyze the potential of electrical energy generated from currents in the Lembeh Strait. Furthermore, an energy potential analysis with CGK Golov Helical TurbineÃ‚Â’s turbine specification. It can produce electrical power from ocean current with a minimum cut-in speed of 0,5 m/s, maximum speed (rated speed) of 1.85 m/s, and maximum produced power of 70.000 W/m2. Hydrodynamic simulations were performed with a 29-day simulation period (March 2016) with bathymetry data input and tidal data for the five open boundary for large models. The potential of current energy in Lembeh Strait is calculated using the Fraenkel equation (1999). The simulation shows the result of power density in one tidal cycle reaching the maximum value at the point between Sarena Island and Sulawesi Island (Point I), that is 72.346,23 W/m2 at full moon condition. The other selected point (Point III) produces a power density of 52.493,31 W/m2. This power is generated using turbine scenario of Gorlov Helical Turbine with design of 0,3 m and 0,544 m rotor diameter.